GAMBARAN KUALITAS INFORMASI ,SHOPPING ENJOYMENT DAN KEPUTUSAN PEMBELIAN PADA FOLLOWERS INSTAGRAM KAMAR GADGET - Muhammad, R. Nur; Wibowo, Lili Adi; Lisnawati, Lisnawati (Journal of Business Management Education (JBME), 2018)
Purpose - The purpose of this study is to see the picture quality of information, shopping enjoyment and purchasing decisionsDesign/methodology/approachh - The design of this study is cross sectional method. This research uses descriptive approach with explanatory survey method. A total of 240 respondents were selected using probability sampling. A questionnaire was used as a research instrument to collect data from respondents. The analysis technique used is descriptive technique by using frequency distribution.Findings - Based on the results of the study using descriptive analysis, the results obtained the quality of information is in very high category with a score of 83.95%, shopping enjoyment and purchase decisions are in high category with a score of 83.88% and 83.30% respectively.Originality/value -Â  This research provides a basis for understanding work environment issues, job satisfaction and employee loyalty. The difference of this research with the previous research is located on the object which is the company of onlineshop Instagram Gadget Room, with the variables studied are the quality of information, shopping enjoyment, and using theory or reference different from previous researchers